Seroprevalence of HIV & HCV coinfection among patients in a rural tertiary care centre in North India - Kaur, Charanjeev (Tropical Journal of Pathology and Microbiology, 2018)
Objective: Viral hepatitis C infection is associated with high morbidity and mortality rates. Chronic HCV infection can cause a wide spectrum of liver disease, potentially leading to severe liver damage, including cirrhosis, organ failure and hepatocellular carcinoma. It accounts for nearly 12– 32% of all cases of liver cancer and 10- 20% cases of cirrhosis of liver, both of which have high treatment costs and poor outcomes. As route of infection of Human Immunodeficiency Virus, Hepatitis B Virus (HBV) and the Hepatitis C Virus (HCV) is same, People with HIV infection are at more risk of acquiring Hepatitis B Virus (HBV) and the Hepatitis C Virus (HCV) infection. The co-infection of Hepatitis C virus with HIV accelerates disease progression and also has an effect on the management of patients infected with HIV. The prevalence of HIV co-infection with Hepatitis C virus varies widely. This study is planned to evaluate the prevalence of HIV co-infection with Hepatitis C viruses in North India. Materials and Methods: A total of 25443 patients enrolled in the microbiology lab were retrospectively analyzed for the presence of HCV and HIV infection on the basis of the presence of anti-HCV and anti HIV markers. Results: In patients infected with HIV, the prevalence of co-infection with HCV was 0.07%. The mean age of the study group was 28.7 years. Discussion: The prevalence rate of HCV are increasing in patients infected with HIV. Having acquired the knowledge about the importance of such a co-infection, it is essential that all the patients infected with HIV be screened for HCV co-infection.